(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The paper highlights the creative career of one of the most outstanding Ukrainian actors and directors Mykola Sadovs’ky (Tobilevych). It is noted that the artist was among the greatest coryphaeuses who being led by M. Kropyvnyts’ky raised the national theater to the highest world level at the end of XIX – the beginning of the 20th century. It is stressed that Mykola Sadovs’ky founded the first Ukrainian resident theater in Kyiv, took active part in the development of the theater in Western Ukraine, in Halychyna and Zakarpattia, created the powerful drama school.